Stem cells enhance reperfusion following ischemia: Validation using laser speckle imaging in predicting tissue repair. (5th February 2018) - Tang, Ya Hui; Thompson, R. Will; Nathan, Cherie‐Ann; Alexander, Jonathan Steven; Lian, Timothy
Abstract : Objectives: The lack of real‐time assessment of vascular perfusion changes remains a major weakness in assessing the efficacy of bone marrow stromal cells (BMSC) therapeutic ischemia reperfusion (I/R) injury. This study provides for the first time the real‐time in vivo perfusion monitoring in I/R mice with BMSC therapy. Study Design: Animal model. Methods: Surgically created cutaneous flaps perfused by the inferior epigastric vessels were subjected to 3.5 hours of ischemia/reperfusion. Wound healing and vascular perfusion were assessed by Image‐J and laser speckle contrast analysis (LSCA) in three groups (sham, I/R, and I/R + BMSC). BMSC tracking was quantified in an additional two groups (with/without I/R) using intravital fluorescent microscopy. The histopathology of skin flaps was examined by hematoxylin and eosin stain. Infiltrated macrophages were analyzed by confocal immunofluorescent microscopy. Results: Postischemic tissues treated with BMSC demonstrated significantly greater survival than I/R control. On days 3 to 7 postreperfusion, both proximal and distal areas in BMSC‐treated flaps demonstrated greater levels of perfusion than untreated I/R flaps ( P < 0.05). Intravital fluorescent microscopy revealed that numbers of labeled BMSC were significantly increased in the distal area compared to the proximal area in both with and without ischemic mice. Histological examination showed lower necrosis and infiltrated inflammatory cells in I/R + BMSC‐treated mice versus I/R controls. Conclusion: BMSC accumulated in I/R flaps and exerted beneficial effects including: 1) improving vascular perfusion and 2) attenuating inflammatory cell infiltration. LSCA facilitates monitoring of the real‐time restitution of perfusion during flap wound healing in experimental animals and could also similarly applied in clinical investigations. Level of Evidence: NA. Laryngoscope, 128:E198–E205, 2018